The technology of communicative training as a means of developing the skills of foreign language intercultural communication of students - Cam, Muhammed Fatih (Вестник Томского государственного университета)
The aim of this study was to present a model of a teaching framework aimed at enriching students' knowledge, skills, and abilities in order to form a foreign language intercultural competence in them through the implementation of communicative intercultural training. The study involved fourth-year students from different countries.